HIGH-PRESSURE GRANULITES: FORMATION, RECOVERY OF PEAK CONDITIONS AND IMPLICATIONS FOR TECTONICS - O'Brien P.J.; Rötzler J. (My University, 2003)
High-pressure granulites are characterised by the key associations garnet-clinopyroxene-plagioclase-quartz (in basic rocks) and kyanite-K-feldspar (metapelites and felsic rocks) and are typically orthopyroxene-free in both basic and felsic bulk compositions. In regional metamorphic areas, two essential varieties exist: a high- to ultrahigh-temperature group and a group representing overprinted eclogites. The high- to ultrahigh-temperature type formerly contained high-temperature ternary feldspar (now mesoperthite) coexisting with kyanite, is associated with garnet peridotites, and formed at conditions above 900 °C and 1.5 GPa. Clinopyroxene in subordinate basic rocks is Al-rich and textural evidence points to a high-pressure–high-temperature melting history. The second variety contains symplectite-like or poikilitic clinopyroxene-plagioclase intergrowths indicating former plagioclase-free, i.e. eclogite facies assemblages. This type of rock formed at conditions straddling the high-pressure amphibolite/high-pressure granulite field at around 700–850 °C, 1.0–1.4 GPa. Importantly, in the majority of high-pressure granulites, orthopyroxene is secondary and is a product of reactions at pressures lower than the peak recorded pressure. In contrast to low- and medium-pressure granulites, which form at conditions attainable in the mid to lower levels of normal continental crust, high-pressure granulites (of nonxenolith origin) mostly represent rocks formed as a result of short-lived tectonic events that led to crustal thickening or subduction of the crust into the mantle. Short times at high-temperature conditions are reflected in the preservation of prograde zoning in garnet and pyroxene. High-pressure granulites of both regional types, although rare, are known from both old and young metamorphic terranes (e.g. c. 45 Ma, Namche Barwa, E Himalaya; 400–340 Ma, European Variscides; 1.8 Ga Hengshan, China; 1.9 Ga, Snowbird, Saskatchewan and 2.5 Ga Jianping, China). This spread of ages supports proposals suggesting that thermal and tectonic processes in the lithosphere have not changed significantly since at least the end of the Archean.
Keywords: disequilibrium; geothermobarometry; high-pressure granulite; mesoperthite; reaction-texture; Precambrian::Archean; Докембрий::Архей